Cryptococcal Disease in the Era of "Test and Treat": Is There Cause for Concern?. (26th December 2017) - Abassi, Mahsa; Rhein, Joshua; Meya, David B; Boulware, David R
Abstract: Treatment of cryptococcosis requires deferred initiation of antiretroviral therapy (ART). Early ART initiation may be detrimental in the context of cryptococcal infection by increasing the risk of immune reconstitution inflammatory syndrome (IRIS). We present 3 cases where early ART initiation in the presence of unrecognized cryptococcal disease had fatal outcomes.